Learning to read with Graphogame, an ethnography in a Peruvian rural school - Ecochard, Sidonie (2015)
The purpose of the present ethnographic case study is to examine what happens when the literacy learning software Graphogame, designed in Finland, is introduced in a new and radically different context, that of a poor rural school in the Peruvian Andes. The research attempts to complement the quantitative approach which has dominated the research on Graphogame. It also aims to take into consideration the unique circumstances and challenges of rural Peru and how they can affect the use and implementation of the software.